BRANDING OF RUMAH SINGGAH TUAN KADI AS A HISTORICAL TOURISM OBJECT OF PEKANBARU CITY - Cahyanti, Ardila Tri; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Branding is a conscious and managed effort to build a good image so that the identity and personality of a place can disappear without branding. Branding is related to trademarks, visual characteristics, logos, images, impressions, characters, and also perceptions or views from visitors about a product. The purpose of this research is to find out the stages of branding implementation and what are the obstacles faced by the Tourism Office as the manager of the Rumah Singgah Tuan Kadi. This study uses a qualitative method with a descriptive approach to describe the actual situation by collecting information data obtained directly from the field. The key informants from this study were three individuals, namely the Head of the Promotion Section of the Pekanbaru City Culture and Tourism Office, supervisors of the Rumah Singgah Tuan Kadi, and visitors. This study uses data collection techniques from literature, observation, documentation and interviews. From this research it can be seen that the branding implementation stages have not been carried out optimally so that many still do not know the historical tourist attraction Rumah Singgah Tuan Kadi.